Systematics and preliminary phylogeny of Bornellidae (Mollusca: Nudibranchia: Dendronotina) based on morphological characters with description of four new species - Pola, Marta; Rudman, William B.; Gosliner, Terrence M. (Zootaxa, 2009)
In this study all available species of the nudibranch family Bornellidae (Bornella Gray, 1850, Pseudobornella Baba, 1932) are re-examined anatomically and their status re-evaluated. Of these, B. hancockana Kelaart, 1859 syn. nov., B. arborescens Pease, 1871 syn. nov., B. caledonica Crosse, 1875a syn. nov., and B. marmorata Collingwood, 1881 syn. nov. are considered to be new synonyms of B. stellifer (Adams and Reeve in Adams, 1848), and B. japonica Baba, 1949 syn. nov. is considered to be a new synonym of B. hermanni Angas, 1864. Two species, B. excepta Bergh, 1884 and B. simplex Eliot, 1904, are at present unrecognizable, B. semperi Crosse 1875b is here considered a nomen nudum, and four new species, B. dotoides sp. nov., B. pele sp. nov., B. valdae sp. nov. and B. johnsonorum sp. nov. are proposed. These are compared with a further four recognized species, B. calcarata Mörch, 1863, B. anguilla Johnson, 1984, B. sarape Bertsch, 1980 and B. irvingi Edmunds and Preece, 1996. The presence of an unpaired oral gland in Bornella is reported for the first time. The reproductive system is diaulic, and the morphology of the penis and the arrangement of the penial spines are considered diagnostic for most species. The monotypic genus Pseudobornella is re-examined for the first time. A comparative table for all recognized species is also provided. The review of the morphological differences within the family provides the basis for a phylogenetic analysis of the group. Bornella is shown to represent a monophyletic clade while the monophyly of the family Bornellidae is not supported.